Electrical and Optical Characteristics of MoOx/ZnO Based Thin Film Photodetector - Kumar H.; Kumar Y.; Rawat G.; Kumar C.; Pal B.N.; Jit S. (My University, 2025)
This work reports the optical characteristics of MoO2/ZnO thin films based ultra-violet (UV) photodetector. The substrate used for the fabrication of UV detector is p-Si over which a thin film of Al2O3 (150 nm) is deposited. Photoactive layer of ZnO thin film (100 nm) is deposited epitaxially over the Al2O3 using spin coating technique. At the top of solution processed ZnO thin film MoO2 (25 nm) is deposited. Aluminum is used as a top (50 nm) and bottom (80 nm) electrode deposited using thermal evaporation. The fabricated device forms a junction between MoO2 and ZnO which is characterized under the monochromatic UV light (650, μW at 365 nm). Th achieved responsivity of the device is 2.33 A/W. Further, the thin film of the ZnO is analyzed for optical characteristics and the obtained band gap is 3.31 eV. © 2019 IEEE.